A multi-stakeholder participatory pilot study of the data demands of the future Ethiopian dairy sector - Perry, Brian D.; Aklilu, Yacob; Hailemariam, Solomon; Legese, Getachew; Smyth, Karen; Peters, Andrew R.; Allan, Fiona K.; Tegegne, Azage (F1000 Research Ltd, 2022)
Background: This paper describes a pilot study undertaken in 2018, to determine the key data needs of each of the different Ethiopian dairy sector stakeholder groups. The study aimed to characterise the emerging trends of dairy product production, processing, retailing and consumption in Ethiopia, and to identify and characterise current and future data needs of different stakeholders.